Integrated epidemiological surveillance in Chad: data from 2010 to 2024 - Ousmane, Kallah Boukar; Agbanlinsou, Arnaud Coffi; Choki, Blaise; Tchibozo, Eyram Maria Concheta; Paraïso, Moussiliou Noël (International Journal Of Community Medicine And Public Health, 2026)
Background: Despite the adoption of the integrated disease surveillance and response strategy (IDSRS), Chad faces various health challenges, particularly regarding the detection and recording of events; case notification; data collection, processing and transmission; and response. The main of this study is to analyse the evolution and effectiveness of the integrated epidemiological surveillance system in Chad between 2010 and 2024. Methods: This is a retrospective descriptive study. It considers the 6 priority diseases with epidemic potential under surveillance in Chad between 2010 and 2024. The main indicator for monitoring the epidemiological situation is the annual case fatality. Results: Between 2010 and 2024 in Chad, meningitis mortality doubled from 6% to 12% despite a decline in cases, while measles (1.1% mortality before 2019) experienced a surge linked to COVID-19, which was quickly brought under control. There were four cholera outbreaks with fatality rates of 3% (2010-2011), 5.8% (2014), 6.4% (2017) and 4.1% (2019). Neonatal tetanus remained rare but highly fatal (approximately 30% mortality on average), and yellow fever had an average mortality rate of 2.7%. Malaria causes approximately 1,843 deaths each year out of more than 1.2 million suspected cases (mortality rate=0.15%). Conclusions: To strengthen Chad’s resilience to epidemiological threats, it is crucial to improve the integration and representativeness of real-time data, training, vaccination coverage, access to difficult areas, infrastructure, and intersectoral coordination, while regularly evaluating the integrated surveillance system.